2016
DOI: 10.3748/wjg.v22.i43.9515
|View full text |Cite
|
Sign up to set email alerts
|

Anti-inflammatory effect of cannabinoid agonist WIN55, 212 on mouse experimental colitis is related to inhibition of p38MAPK

Abstract: AIMTo investigate the anti-inflammatory effect and the possible mechanisms of an agonist of cannabinoid (CB) receptors, WIN55-212-2 (WIN55), in mice with experimental colitis, so as to supply experimental evidence for its clinical use in future.METHODSWe established the colitis model in C57BL/6 mice by replacing the animals’ water supply with 4% dextran sulfate sodium (DSS) for 7 consecutive days. A colitis scoring system was used to evaluate the severity of colon local lesion. The plasma levels of proinflamma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 23 publications
2
17
0
Order By: Relevance
“…Our data suggested the involvement of p38 MAPK signaling in CB2 receptor‐mediated regulation of intestinal motility in stress‐induced IBS. These results are in agreement with previous reports on the close association between CB2 receptors and p38 MAPK inhibition, suggesting that CB2 receptors are coupled to MAPK through G proteins and regulate MAPK phosphorylation . Our data are also in line with the finding that p38 MAPK is required for the production of IBS‐like symptoms .…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…Our data suggested the involvement of p38 MAPK signaling in CB2 receptor‐mediated regulation of intestinal motility in stress‐induced IBS. These results are in agreement with previous reports on the close association between CB2 receptors and p38 MAPK inhibition, suggesting that CB2 receptors are coupled to MAPK through G proteins and regulate MAPK phosphorylation . Our data are also in line with the finding that p38 MAPK is required for the production of IBS‐like symptoms .…”
Section: Discussionsupporting
confidence: 94%
“…One potential explanation may be that chronic stress directly regulates the colon ECS via the brain-gut axis through key alterations in the inhibition, suggesting that CB2 receptors are coupled to MAPK through G proteins and regulate MAPK phosphorylation. 29 Our data are also in line with the finding that p38 MAPK is required for the production of IBS-like symptoms. 30 Nitric oxide (NO), produced by nNOS, is a major GI inhibitory neurotransmitter.…”
Section: Discussionsupporting
confidence: 90%
“…MAPK signaling is associated with nuclear factor NF-κB, one of the transcription factors. In particular, the phosphorylation of p38 and ERK induces activation of NF-κB with many direct and indirect interactions [45,46]. Both GL and GH treatment groups showed significant results, indicating a role in reducing inflammatory factors (Figure 8).…”
Section: Resultsmentioning
confidence: 97%
“…Mouse model studies have shown an incremental therapeutic benefit of both cannabidiol and THC over sulfasalazine in reducing inflammation and functional symptoms (Jamontt, Molleman, Pertwee, & Parsons, ). A possible mechanism of action of the colonic anti‐inflammatory effect of CB receptor activation is the inhibition of p38‐mitogen‐activated protein kinase signalling, as shown in studies of the nonselective CB receptor agonist WIN55,212 using a murine model of dextran sulfate sodium‐induced colitis (Li et al, ; Feng, Li, Lin, Li, & Cao, ; Table ). A recent meta‐analysis of 34 animal studies reporting the effects of cannabinoid drugs on disease activity index (DAI) or myeloperoxidase activity in various models of mouse or rat colitis concluded that these drugs are beneficial in treating this kind of experimental disease, which warrants the undertaking of appropriate clinical trials (Couch, Maudslay, Doleman, Lund, & O'Sullivan, ).…”
Section: Cannabismentioning
confidence: 99%